2000
DOI: 10.1111/j.1349-7006.2000.tb00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Oxidative DNA Damage and Its Repair Activity in the Livers of 3′‐Methyl‐4‐dimethylaminoazobenzene‐treated Rodents

Abstract: We measured the levels of 8‐hydroxyguanine (8‐OH‐Gua) and its repair activity in the livers of the Donryu rat, the carcinogen‐resistant DRH rat, and the ddy mouse, which were fed a 0.06% 3′‐ methyl‐4‐dimethylaminoazobenzene (3′‐MeDAB)‐containing diet. In a short‐term rat experiment (maximum 2 months), 3′‐MeDAB did not increase the 8‐OH‐Gua levels in the livers of the two rat strains, although it significantly increased the repair activity in only the Donryu rat liver at 1 and 2 months. After long‐term 3′‐MeDAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…4, we confirmed that mOGG1-32 contains these regions. It is noteworthy that our previous observations indicated that the 8-OH-Gua excision repair activity in mouse liver was increased by up to 1.6-fold by treatment with 3′-MeDAB, 7) whereas the relative intensity of the 38-kDa mOGG1 showed no significant difference between the carcinogen-treated and control groups (Fig. 3B-a).…”
Section: Discussionmentioning
confidence: 60%
“…4, we confirmed that mOGG1-32 contains these regions. It is noteworthy that our previous observations indicated that the 8-OH-Gua excision repair activity in mouse liver was increased by up to 1.6-fold by treatment with 3′-MeDAB, 7) whereas the relative intensity of the 38-kDa mOGG1 showed no significant difference between the carcinogen-treated and control groups (Fig. 3B-a).…”
Section: Discussionmentioning
confidence: 60%
“…5,6) Experiments in both cultured cells and animals have supported this premise. [7][8][9][10][11] Therefore, analyses of oxidative DNA damage should be useful to understand in detail the mechanisms of carcinogenesis. Moreover, the genes for the human and mouse glycosylase-type repair enzymes for 8-OHGua (hOGG1 and mOGG1) have been cloned.…”
mentioning
confidence: 99%
“…[12][13][14] The corresponding proteins have also been analyzed to study the mechanisms of carcinogenesis and to assess the cancer risks of chemical substances or environmental factors. [7][8][9][10][11] Several recent reports have suggested a relationship between oxidative DNA damage and the apoptotic process, [15][16][17] although, to our knowledge, only a few studies have investigated the relationship between 8-OH-Gua and apoptosis. Apoptosis is a physiological process of programmed cell death, which is characterized by distinct morphological changes and internucleosomal DNA fragmentation.…”
mentioning
confidence: 99%
“…Some of them, such as N-methyl-4-aminoazobenzene, N, N-dimethyl-4-aminoazobenzene, and 3'-methyl-4-dimethylaminoazobenzene (3'-MeDAB), are hepato-carcinogenic. We previously analyzed the effects of 3'-MeDAB on 8-oxo-Gua repair systems in rodent livers, and reported that 3'-MeDAB increased 8-oxo-Gua generation and decreased OGG1 expression, possibly by cleaving the protein [22]. These results suggested that the liver carcinogenicity of 3'-MeDAB was due to an increase in 8-oxo-Gua generation via 3'-MeDABinduced downregulation of OGG1 expression.…”
Section: Aminoazo Dyes and 8-oxo-gua / Ogg1mentioning
confidence: 93%
“…The decrease in the 8-oxo-Gua repair activity seems to be a reasonable consequence of the lower 8-oxo-Gua levels. Since we speculated that OGG1 fragmentation was a key event for 3'-MeDAB-induced 8-oxo-Gua accumulation [22], we predicted that OGG1 fragmentation might be inhibited by ethanol intake, as in the inhibition of the increase in 8-oxo-Gua levels. However, 12% ethanol intake failed to inhibit the 3'-MeDAB-induced fragmentation of OGG1 (groups D, E, and F in Fig.…”
Section: Alcohol and 8-oxo-gua / Ogg1mentioning
confidence: 99%